Postural function of the diaphragm in persons with and without chronic low back pain - Kolar, Pavel; Sulc, Jan; Kyncl, Martin; Sanda, Jan; Cakrt, Ondrej; Andel, Ross; Kumagai, Kathryn; Kobesova, Alena (The Journal of orthopaedic and sports physical therapy, 2012)
STUDY DESIGN: A case-control study. OBJECTIVES: To examine the function of the diaphragm during postural limb activities in patients with chronic low back pain and healthy controls. BACKGROUND: Abnormal stabilizing function of the diaphragm may be an etiological factor in spinal disorders. However, a study designed specifically to test the dynamics of the diaphragm in chronic spinal disorders is lacking. METHODS: Eighteen patients with chronic low back pain due to chronic overloading, as ascertained via clinical assessment and magnetic resonance imaging, and 29 healthy subjects were examined. Both groups presented with normal pulmonary function test results. A dynamic magnetic resonance imaging system and specialized spirometric readings were used with subjects in the supine position. Measurements during tidal breathing (TB) and isometric flexion of the upper and lower extremities against external resistance with TB were performed. Standard pulmonary function tests, including respiratory muscle drive (PI(max) and PE(max)), were also assessed. RESULTS: Using multivariate analysis of covariance, smaller diaphragm excursions and higher diaphragm position were found in the patient group (P<.05) during the upper extremity TB and lower extremity TB conditions. Maximum changes were found in costal and middle points of the diaphragm. A 1-way analysis of covariance showed a steeper slope in the middle-posterior diaphragm in the patient group both in the upper extremity TB and lower extremity TB conditions (P<.05). CONCLUSION: Patients with chronic low back pain appear to have both abnormal position and a steeper slope of the diaphragm, which may contribute to the etiology of the disorder.
Keywords: respirační funkční testy; Low Back Pain; bránice; Male; Chronic Disease; chronická nemoc; Middle Aged; Postural Balance; břišní svaly; mužské pohlaví; Abdominal Muscles; studie případů a kontrol; Adult; mladý dospělý; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Young Adult; ženské pohlaví; Humans; Respiratory Function Tests; lidé středního věku; Diaphragm; lumbalgie; posturální rovnováha; dospělí; Female; lidé; Case-Control Studies